2019
DOI: 10.21203/rs.2.11718/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The efficacy and safety of 'Antianxiety Granule' for anxiety disorder: A multicentre, randomized, double-blind, placebo-controlled, parallel-group trial

Abstract: Background: Anxiety disorders are the most prevalent class of lifetime disorders in China, and generalized anxiety disorder (GAD) is one of the most common but frequently overlooked anxiety disorders. Conventional pharmacological treatments for GAD have varying degrees of side effects, dependency, and/or withdrawal syndromes. Traditional Chinese Medicine (TCM) therapy is considered a valuable therapeutic option for anxiety disorders and a potentially effective technique to reduce the side effects associated wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…[5] As the working ability of GAD patients decreases, with the increasing social pressure and the lack of effective anxiety management, more medical resources will be used, this will undoubtedly increase the social burden and the economic pressure of GAD patients. [6] In the current clinical practice, pharmacological intervention is one of the main treatment methods of GAD, mainly include selective serotonin reuptake inhibitors and serotonin norepinephrine reuptake inhibitors. [7] However, these pharmaceuticals may not be well tolerated in patients with GAD, some studies have shown that both selective serotonin reuptake inhibitors and serotonin norepinephrine reuptake inhibitors are related to the decline of efficacy at high doses.…”
Section: Introductionmentioning
confidence: 99%
“…[5] As the working ability of GAD patients decreases, with the increasing social pressure and the lack of effective anxiety management, more medical resources will be used, this will undoubtedly increase the social burden and the economic pressure of GAD patients. [6] In the current clinical practice, pharmacological intervention is one of the main treatment methods of GAD, mainly include selective serotonin reuptake inhibitors and serotonin norepinephrine reuptake inhibitors. [7] However, these pharmaceuticals may not be well tolerated in patients with GAD, some studies have shown that both selective serotonin reuptake inhibitors and serotonin norepinephrine reuptake inhibitors are related to the decline of efficacy at high doses.…”
Section: Introductionmentioning
confidence: 99%